2015
DOI: 10.1021/acscatal.5b00235
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum(salen) Complexes as Catalysts for the Kinetic Resolution of Terminal Epoxides via CO2 Coupling

Abstract: The development of inexpensive and sustainable aluminum­(salen) complexes as catalysts for the kinetic resolution of terminal epoxides is described. The kinetic resolution is carried out under mild conditions (0–25 °C and 1 bar of CO2 pressure) in the presence of tetrabutylammonium bromide as co-catalyst in the absence of solvent. The relative rate of reaction of the two epoxide enantiomers (k rel) is substrate dependent, and the highest k rel obtained was 15.4, using N-(2,3-epoxypropyl)­diphenylamine as subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(84 citation statements)
references
References 45 publications
2
77
0
Order By: Relevance
“…Generally, salen‐based aluminum complexes have poor solubility in common organic solvents , . Thus, many salen‐based aluminum catalysts for the coupling of CO 2 and epoxides have a tert ‐butyl group at the 3‐position of the phenolate ring to improve their solubility in epoxides, which are common solvents for this transformation . Until now, aluminum complexes containing a methyl group at the 3‐position of the phenolate ring of the salen ligands have never been reported as catalysts for the cycloaddition of CO 2 to epoxides.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, salen‐based aluminum complexes have poor solubility in common organic solvents , . Thus, many salen‐based aluminum catalysts for the coupling of CO 2 and epoxides have a tert ‐butyl group at the 3‐position of the phenolate ring to improve their solubility in epoxides, which are common solvents for this transformation . Until now, aluminum complexes containing a methyl group at the 3‐position of the phenolate ring of the salen ligands have never been reported as catalysts for the cycloaddition of CO 2 to epoxides.…”
Section: Resultsmentioning
confidence: 99%
“…Finding new catalyst systems for the coupling of CO 2 with epoxides to make cyclic carbonates, which have broad applications as aprotic solvents, electrolytes for lithium‐ion batteries, monomers for polymers, and pharmaceutical intermediates, is one of the most active research areas in CO 2 conversion A variety of catalyst systems have been reported for this transformation, among which nontoxic catalysts based on earth‐abundant aluminum are among the most significant . Bidentate benzotriazole phenoxides, bidentate pyrazole‐based scorpionates, bidentate 8‐hydroxyquinoline,, tetradentate triphenolateamine, tetradentate porphyrin, tetradentate salen, tetradentate salenac, salalen,, and bidentate/tridentate/tetradentate aliphatic amino alcohols, have all been used extensively as chelating ligands ...…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, North et al have reported the use of aluminium(III) and chromium(III) salen complexes for the kinetic resolution of terminal epoxides via carbon dioxide coupling (Figure 4) [27]. It is worth highlighting that they have reported the first aluminium-based catalysts capable of performing the kinetic resolution of epoxides by carbon dioxide coupling for the synthesis of enantiomerically enriched cyclic carbonates.…”
Section: Other Metal Salen Complexesmentioning
confidence: 99%